Novel chromium imprinted polymer: synthesis, characterization and analytical applicability for the selective remediation of Cr(VI) from an aqueous system. Issue 5 (9th April 2019) - Kumar, Ameet; Balouch, Aamna; Pathan, Ashfaque Ahmed; ., Abdullah; Jagirani, Muhammad Saqaf; Mahar, Ali Muhammad; Rajput, Manzoor-Ul-Haq
ABSTRACT: In this study, we report the synthesis of chromium imprinted polymer (Cr-IP) by a simple and facile one-pot precipitation polymerization technique by using 1-vinyl imidazole as ligand and methacrylic acid as functional monomer and their application for the specific removal of toxic hexavalent chromium from aqueous media. To attain maximum adsorption capacity various components i.e. functional monomer, cross-linker, and the molar ratio of ligand, monomer, and cross-linker were evaluate. Furthermore, several parameters i.e. pH, adsorbent dose, agitation time and shaking speed were also optimized to obtained maximum adsorption efficiency. The synthesized Cr-IP was characterized by SEM, EDX and FT-IR. The kinetic data were well described by pseudo-second-order while Langmuir model is best fitted to isotherm data. The maximum adsorption capacity of Cr-IP was 76.92mg/g. The relative standard deviation, limit of detection and quantification of this method was found to be 4.7%, 0.71µg/L and 2.36µg/L. The relative selective coefficient of Cr(VI) ions and competitive ions is greater than one due to the imprinting effect. This Cr-IP polymer also possesses good reproducibility and stability. The synthesized imprinted polymer has successfully applied for elimination of toxic Cr(VI) from real water samples.